DELLAs Contribute to Set the Growth and Mineral Composition of Arabidopsis thaliana Plants Grown Under Conditions of Potassium Deprivation - Oliferuk, Sonia (2017)
DELLAs proteins play a major role in the modulation of plant responses to fluctuations in environmental conditions. In this work, we examined to what extent Arabidopsis thaliana plants lacking DELLAs activity (5xdella mutant) or carrying an altered function allele of one of the DELLAs coding genes (gai-1 mutant) display differential responses, in terms of growth and shoot elemental composition, relative to WT plants when deprived of potassium (K). Studies with plants grown in hydroponic media unveiled that the shoot mineral composition of gai-1 constitutively differs from that of WT and 5xdella plants. Tolerance to K-deprivation, as estimated by the relative decline of biomass accumulation, followed the order gai-1 > WT > 5xdella. In turn, the degree of responsiveness of the shoot composition to the stress condition followed the order 5xdella > WT > gai-1, suggesting a correspondence between the degree of injury and changes in the elemental composition. Internal efficiency of K-utilization was maximized in WT relative to 5xdella plants. Interestingly, the acquisition of K was severely impaired in gai-1 plants well supplied, or deprived of, K. Complementary studies indicated that influx and root-to-shoot transport of Rubidium, a K-analogue, were reduced in those plants. Furthermore, evidence obtained supports the view that the effect of altered DELLAs derives, at least partially, from controlling the accumulation of transcripts coding for the AtHAK5 transporter. These results, together with the observation that K-deprivation promotes the accumulation of a DELLA protein (RGA) fused to GFP in root cells, suggest a pivotal role of DELLAs in key plant responses to K-deprivation.